BIOLOGI BUNGA TUMBUHAN NEPENTHES (N. ampullaria, N. Gracilis, dan N. Reinwardtiana.) (Jurnal Pelangi : Research of Education and Development, 2012)
ABSTRACTNepenthes is a dioecious plant, that are male flowers and female flowersare separated on different individuals. Consider the threat of extinction of plantspecies of high economic value, conservation it is necessary with cultivation.Nepenthes cultivation mostly through seeds because growth through stem cuttingsis still very low. Then has done research on the biology of Nepenthes ampullaria,N. gracilis, and N. reinwardtiana. Research has been carried out from Juni 2009to Juni 2010. Androecium collected from Taratak Pesisir Selatan, Palupuh, andHPPB Andalas University Padang. Research method is a method of observationthat includes aspects of the pattern of blooming flowers. Samples taken from theoriginal habitat of flowers that bloom from the male flowers. From the resultshowed that the pattern of male flowers blooming N. ampullaria, N. garcilis andN. reinwardtiana acropetal generally the same, namely, the process of bloomingflowers in a stalk during the week and time anthesis from dawn to dusk, exceptanther dehiscens on N. ampullaria occurred several hours after the floweranthesis, whereas in N. gracilis and N. reinwardtiana immediately after theflowers anthesis. Male flowers N. ampullaria evenly bloom each flower on agroup of flower, sequentially from base to tip. After one stage of bloom, followedby a second bloom in the flower. So on until all the flowers bloom. Male flowersN. gracilis blossom one by one while at N. reinwardtiana flowers bloom ingroups, one group completed a new, gradual upward. On N. gracilis and N.reinwardtiana anthesis interest rates start to bloom at the time, whereas in N.ampullaria anthesis interest after the color changes from red to yellow.